Effects of High-Density Electric Current Pulse on the Undercooling of Fe-B Eutectic Alloy Melt - Teng Ma; Weixin Hao; Xiaosi Sun; Junting Zhang; Guihong Geng (Advances in Materials Science and Engineering)
The solidification microstructure of Fe-B eutectic alloy under high undercooling and high-density electric current pulse (ECP) was investigated with the technique of molten glass slag purification combined with cyclical superheating and the ECP treatment. The effects of high-density ECP on the undercooling of Fe-B eutectic alloy melt were analyzed by the DSC method. The analysis results showed that the solidification microstructure of Fe-B eutectic alloy under ECP was similar to that obtained by the high undercooling technique. The undercooling obtained under two experimental conditions was basically the same, proving that the high undercooling of the metallic melt could be realized by the ECP.